The EQo-Mental project: A protocol for a mixed-methods study on occupational balance and mental health in parents of children with developmental delays - Desirée Valera-Gran; Miriam Hurtado-Pomares; Iris Juárez-Leal; Rocío Muñoz-Sánchez; Irene Campos-Sánchez; Paula Noce; Jessica Piñero; Eva-María Navarrete-Muñoz (PLoS ONE, 2025)
Background Parents of children with developmental delays (DD) often face significant challenges that affect their mental health and occupational balance. While early intervention services traditionally focus on child development, the occupational needs and well-being of parents remain underexplored. The EQo-Mental project aims to examine the association between parental mental health, occupational balance, and meaningful activity engagement, and to co-develop family-centred strategies that promote well-being in early intervention contexts. Methods This sequential mixed-methods study includes two phases. The quantitative phase will involve approximately 700 parents of children aged 0–6 years attending early intervention centres in Alicante, Spain. This phase comprises two components: (1) the psychometric validation of the Spanish versions of two occupational measures—the Occupational Balance Questionnaire (OBQ-E) and the Engagement in Meaningful Activities Survey (EMAS)—and (2) a cross-sectional analysis examining associations between occupational and mental health outcomes. Participants will complete a sociodemographic questionnaire along with validated self-administered instruments assessing occupational balance, meaningful activity engagement, stress, anxiety, depression, and psychological well-being. In the qualitative phase, participatory sessions and focus groups will be conducted with a subsample of parents and key stakeholders to explore perceived occupational and mental health needs and to co-design actionable strategies for improving occupational balance and family well-being. Participant recruitment began in November 2023 and is ongoing; data collection is expected to be completed by October 2025. Analyses Psychometric analyses will first be conducted to evaluate the validity and reliability of the OBQ-E and EMAS. Next, descriptive analyses and multiple regression models adjusted for potential confounders will be used to explore associations between occupational and mental health variables. Phase 2 consists of a participatory-action research process, including discussion groups and a multi-stakeholder focus group. Qualitative data will be analysed using reflexive thematic analysis. Outcomes Findings from EQo-Mental will inform the design of evidence-based, family-centred strategies that support occupational balance, parental well-being, and engagement in meaningful activities. By addressing the occupational needs of parents, the project seeks to foster more resilient families and strengthen early intervention services through an inclusive, occupation-focused approach.